2013
DOI: 10.1002/adsc.201300828
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine‐Catalyzed Asymmetric [4+2] Annulation of Vinyl Ketones with Oxindole‐Derived α,β‐Unsaturated Imines: Enantioselective Syntheses of 2′,3′‐Dihydro‐1′H‐spiro[indoline‐3,4′‐pyridin]‐2‐ones

Abstract: A novel asymmetric [4+2] annulation of vinyl ketones with oxindole-derived a,b-unsaturated imines has been developed in the presence of a multifunctional thiourea-phosphine catalyst derived from a natural amino acid, providing the first phosphine-catalyzed enantioselective synthesis of 2',3'dihydro-1'H-spiro[indoline-3,4'-pyridin]-2-ones in good yields with excellent stereoselectivities under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…Very recently, Shi′s group envisioned that isatin‐based spiro‐fused six‐membered heterocyclic skeletons with two stereocenters could be constructed through the [4+2] annulation of vinyl ketones with oxindole‐derived α,β‐unsaturated imines 37. They screened a series of chiral phosphines and found that amino‐acid‐derived chiral thiourea‐phosphine 49 was the best catalyst for this reaction.…”
Section: Cycloaddition Reactions Of Activated Allenes Alkenes Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Shi′s group envisioned that isatin‐based spiro‐fused six‐membered heterocyclic skeletons with two stereocenters could be constructed through the [4+2] annulation of vinyl ketones with oxindole‐derived α,β‐unsaturated imines 37. They screened a series of chiral phosphines and found that amino‐acid‐derived chiral thiourea‐phosphine 49 was the best catalyst for this reaction.…”
Section: Cycloaddition Reactions Of Activated Allenes Alkenes Anmentioning
confidence: 99%
“… Enantioselective [4+2] annulation of vinyl ketones with oxindole‐derived α,β‐unsaturated imines 37. TMS=trimethylsilyl.…”
Section: Cycloaddition Reactions Of Activated Allenes Alkenes Anmentioning
confidence: 99%
“…Scheme 61 A plausible mechanism for the tandem Rauhut-Currier/ Michael/Rauhut-Currier reaction Shi, Wei and co-workers synthesized 2′,3′-dihydro-1′H-spiro[indoline-3,4′-pyridin]-2-one derivatives, starting from oxindole-derived α,β-unsaturated imines and methyl vinyl ketone 57 A. Voituriez et al…”
Section: Cycloaddition Reactions Involving Methyl Vinyl Ketone Derivamentioning
confidence: 99%
“…356 Wei and Shi developed a [4 + 2]-cycloaddition of vinyl ketones and α,β-unsaturated imines derived from isatins catalysed by a bifunctional asymmetric phosphorus-thiourea catalyst (Scheme 72, R = 2,4,6-triisopropyl phenyl). 357 In metalmediated approaches, gold catalysed spirocyclisation of in situ generated indoles and isatins was reported by Subba Reddy. 358 Related to Liu and Feng's reaction (ref.…”
Section: Spiropiperidinyl Oxindolesmentioning
confidence: 99%